Studi Faktor Pemulihan Pariwisata Budaya Kota Bandung Era Covid-19 - Novanda Jessa Charda; Weishaguna (UNISBA Press, 2022)
Abstrack. The Wold Health Organization has determined that Covid-19 is a pandemic that is dangerous to human life due to its very fast and massive transmission, in the city of Bandung as one of the most cases of transmission, causing problems for the tourism destination sector which cannot operate because it is temporarily closed because it belongs to the non-essential sector, so the purpose of this study is to find out in what quadrant the tourism recovery is and the key factors for its recovery. The qualitative approach is the concentration of the study, using the method of analyzing strengths, weaknesses, opportunities, and threats to program planning variables to reduce risk, preparation of standby programs, response preparation programs, and programs to return to their original conditions on the criteria of crisis awareness indicators, security awareness, standards operational procedures, crisis management, tourism planning, health and safety measures, emergency response procedures, investigations, assistance and communication, tourism continuation, human resource-debriefing. From the results of the analysis, this study finds that the position of tourism in Bandung is in quadrant I, namely supporting aggressive steps, meaning being optimistic internally and externally as a guide in affirming the direction of improving recovery, while assessing the position of key factors owned by tourism objects and the relevant government towards recovery. met at the indicators of crisis awareness and communication assistance that had been adaptive and responsive was carried out in the Covid-19 pandemic situation. Abstrak. Wold Health Organization menetapkan Covid-19 menjadi sebuah pandemi yang membahayakan bagi kehidupan umat manusia disebabkan penularanya yang sangat cepat dan masif, di Kota Bandung sebagai salah satu kasus penularan terbanyak memberi masalah pada sektor destinasi pariwisata yang tidak dapat beroprasi sebab di tutup sementara karena tergolong pada sektor non-esensial, sehingga tujuan studi ini guna menemukan pada posisi kuadran apa pemulihan pariwisata beserta faktor kunci pemulihanya. Pendekatan kualitatif menjadi konsentrasi studi, dengan menggunakan metode analisis kekuatan, kelemahan, peluang, dan ancaman kepada variabel perencanaan program untuk mengurangi risiko, persiapan program siaga, program persiapan respons, dan program pengembalian ke kondisi semula terhadap kareteria indikator kesadaran krisis, kesadaran keamanan, standar oprasional procedure, manajemen krisisi, perencanaan pariwisata, tindakan kesehatan dan keselamatan, prosedur tanggap darurat, investigasi, bantuan dan komunikasi, kelanjutan pariwisata, sdm-pembekalan. Dari hasil analisis, studi ini menemukan posisi kepariwisataan Kota Bandung berada di kuadran I yakni mendukung pada langkah agresif, artinya optimis secara internal dan eksternal sebagai petunjuk dalam mempertegas arah meningkatkan pemulihan, sementara penilaian kedudukan faktor kunci yang di miliki objek pariwisata dan pemerintah terkait menuju pemulihan bertemu pada kareteria indikator kesadaran krisis dan bantuan komunikasi yang telah adaptif serta responsif di laksanakan dalam situasi pandemi Covid-19.